Implikasi Hukum Praktik Investasi Asing Yang Berkaitan Dengan Alih Teknologi Dalam Rezim Paten - Rintus Leonardo T Sibero (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The problem of technology transfer is a problem that is always faced by developing countries, including Indonesia. Because Indonesia has directed its economic development by focusing on the industrial sector, until the industrial sector becomes the backbone of the national economy. This study aims to determine the forms of technology transfer in investment and the procedures for transferring technology in investment activities in Indonesia. The method used in this research is normative juridical to analyze legal issues contained in laws and regulations related to the problem under study with qualitative analysis. The results show that foreign investment and technology transfer are two things that cannot be separated. Technology transfer or what is often referred to as technology transfer includes, products, production processes and machines. Technology transfer procedures can be carried out by hiring foreign experts individually, providing supplies of machinery and other equipment. Legal implications in technology transfer can occur in various forms, such as license agreements in technology, technology owners can facilitate technology by giving rights to any person / entity to implement technology with licenses, expertise and technological assistance.